Blue Ocean Leadership : Bagaimana Pemimpin Menciptakan Pasar Baru yang Bebas dari Persaingan - Fikri Dwi Novianto; Rahma Amelia; Fatimatus Zahro; Mochammad Isa Anshori (Jurnal of Management and Social Sciences, 2025)
"Blue Ocean Leadership" is a strategic approach that aims to create a new market that is free from competitors by focusing on innovation and value creation. In the context of increasingly competitive businesses, many organizations are trapped in a "sea of red," where fierce competition leads to declining profit margins. This concept invites leaders to move to the "blue ocean," which is an unexplored market space where demand can be created rather than simply shared. Through visionary and creative leadership, leaders can encourage teams to identify new opportunities, design unique products or services, and deliver unparalleled customer experiences. Leadership in the context of Blue Ocean also involves developing an organizational culture that supports innovation, collaboration, and continuous learning. By empowering employees to think outside conventional boundaries, organizations can find solutions that not only meet customer needs but also create greater value. This approach is not only financially profitable, but it also contributes to the company's long-term sustainability in the face of market changes. Overall, Blue Ocean Leadership offers a relevant framework for leaders to design effective strategies in creating new markets that are sustainable and free from competitors.